Kepengasuhan Santri di Pondok Pesantren Tahfidz Nurul Qur'an Karanganyar - Anshory, Isa; Solikhah, Hanik Rahmawati; Efendi, Asmira; Mujahidah, Anny Izzatul (Darul Yasin Al Sys, 2025)
Islamic boarding schools have unique parenting characteristics compared to other educational environments. Parenting patterns are usually based on Islamic values ​​and are focused on strengthening aqidah, forming noble morals, discipline and independence of students. Parenting patterns in Islamic boarding schools also vary depending on the traditions and approaches of each Islamic boarding school. Therefore, it is very interesting to take research on parenting patterns at the Tahfidz Nurul Quran Islamic Boarding School, Jaten Karanganyar. This research is field research using field observation methods and interviews with Islamic boarding school owners.